Om nordisk musikk: Tim Howell, red., 2020. The nature of Nordic music. Abingdon: Routledge. xxii+250 s. ISBN: 978-1-138-20718-9 (hardback), 978-0-367- 77707-4 (paperback), 978-1-315-46285-1(e-bok). - Dyndahl, Petter (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2023)
Review of Tim Howell, ed., 2020. The nature of Nordic music. Abingdon: Routledge. xxii+250 pp. ISBN: 978-1-138-20718-9 (hardback), 978-0-367- 77707-4 (paperback), 978-1-315-46285-1(e-book). The review is written in Norwegian.